2010
DOI: 10.1002/masy.201051057
|View full text |Cite
|
Sign up to set email alerts
|

Water‐Soluble Polyelectrolytes with Ability to Remove Arsenic

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Most of the successful arsenic removal processes reported so far rely on the ion exchange mechanism [5,19]. This can be ascribed to multi-negative charges of arsenious and arsenite species.…”
Section: Arsenic Removal Characteristic Of the Cationic Hydrogelmentioning
confidence: 99%
See 4 more Smart Citations
“…Most of the successful arsenic removal processes reported so far rely on the ion exchange mechanism [5,19]. This can be ascribed to multi-negative charges of arsenious and arsenite species.…”
Section: Arsenic Removal Characteristic Of the Cationic Hydrogelmentioning
confidence: 99%
“…In particular, it was observed that polymers with quaternary amine groups were effective for removing As(V) during membrane-assisted studies [1][2][3][4][5][6][13][14][15]. Rivas et al [5] reported the successful removal of arsenic with various watersoluble polymers combined with ultra-filtration using (R) 4 N + X À groups. Linear poly(diallyldimethylammonium chloride) (DAD-MAC) is included among the polymers with proven effectiveness for removing As(V).…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations